2017
DOI: 10.1055/s-0037-1606551
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Endoscopic-Assisted Transoral and Transnasal Approaches to Parapharyngeal Space: A Cadaveric Study

Abstract: Surgical resection of parapharyngeal space (PPS) tumors is very challenging. An endoscopic-assisted surgical approach to this region requires detailed and precise anatomic knowledge. The main purpose of this study is to describe and compare the detailed anatomy of the PPS via transnasal transpterygoid (TP) and endoscopic-assisted transoral (TO) approaches. Six fresh injected cadaver heads (12 sides) were prepared for dissection of the PPS via TP and TO approaches. Computed tomography (CT) with image-based navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 22 publications
1
46
0
10
Order By: Relevance
“…Each cadaveric head was injected with colored silicone; red silicone for the arterial system and blue for the venous system. Endoscopes (0° and 30°) coupled with a high-definition camera and an AIDA HD system (Karl Storz GmbH and Co.) were used to provide excellent visualization [3]. Stepwise dissection via the combined endoscopic transnasal and anterior transmaxillary approach was performed to present the landmarks of the upper PPS and the middle skull base.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each cadaveric head was injected with colored silicone; red silicone for the arterial system and blue for the venous system. Endoscopes (0° and 30°) coupled with a high-definition camera and an AIDA HD system (Karl Storz GmbH and Co.) were used to provide excellent visualization [3]. Stepwise dissection via the combined endoscopic transnasal and anterior transmaxillary approach was performed to present the landmarks of the upper PPS and the middle skull base.…”
Section: Methodsmentioning
confidence: 99%
“…Retracting the MPM and TVPM laterally was helpful to expose the levator veli palatini muscle (LVPM). The soft tissue between the TVPM and superior pharyngeal constrictor muscle was removed to expose the medial space of upper PPS, as described in our previous report [3]. The medial space of the upper PPS was dissected posteriorly to access the poststyloid compartment.…”
Section: Exposure Of the Upper Pps And The Middle Cranial Basementioning
confidence: 99%
See 2 more Smart Citations
“…The goal of surgery is complete removal of tumors with minimal morbidity. Many surgical routes to PPS have been described, from the classic surgical approaches (cervical, transparotid, cervical‐parotid with or without mandibulotomy, preauricular, and infratemporal fossa approaches) to the endoscope‐assisted transnasal/transoral/transvestibular corridors, and combinations of these approaches . Ferrari et al recently reported a complete spectrum of anatomic routes to PPS .…”
mentioning
confidence: 99%